Studies on the Effects of Cold Starts of the Ship Main Engine - Adamkiewicz Andrzej; Fydrych Janusz; Drzewieniecki Jan (Polish Maritime Research, 2022)
This article presents the influence of various ship’s operational conditions occurring during manoeuvres related to entering and leaving the ports and mooring operations. Frequent starts and stops of the ship’s propulsion unit are then required, which affect the variability of the energetic loads of the ship’s power plant, causing accelerated, non-design wear of the ship’s main propulsion engine. The effects of cold start-ups of the main ship engine are the subject of this study. Conditions of the engine inlet valve damage process are discussed. The physics of the degradation process leading to air inlet valve damage was considered. Laboratory tests of structure continuity and their results are discussed, and the valve material defects were excluded as the cause of the damage. The causes of repeated damage to the inlet air valves were identified. The effectiveness of the performed corrective measures was confirmed by a documented control test of the engine start-up. The article is a utilitarian premise for the requirements of the Classification Society.